2022
DOI: 10.1186/s12891-022-05080-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of 21,194 UKAs and 49,270 HTOs for the risk of unanticipated events in mid-age patients from the national claims data in South Korea

Abstract: Background Both high tibial osteotomy (HTO) and unicompartmental knee arthroplasty (UKA) are well-established treatments for medial knee osteoarthritis (OA). However, over the past 20 years, results of comparisons of long-term survival rates and outcomes have remained controversial. Furthermore, in patients at the boundary age, from 50 to 70 years, considering age as a treatment indication, selecting a surgical method is difficult. Therefore, we aimed to investigate conversion rates to total kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…13,42 In a study of 70,464 patients aged between 50 and 70 years from the Korean National Health Insurance claims database, HTO showed a higher risk of reoperation than UKA at 10-year follow-up, while postoperative DVT and SSI were significantly higher in UKA than in HTO. 19 A retrospective comparative study including patients from the Military Health System also demonstrated that HTO was associated with a higher reoperation rate when compared with UKA. 27 Stukenborg-Colsman et al 36 conducted one of the few relevant randomized controlled trials that can be identified in the literature, comparing 32 patients treated with HTO and 28 patients treated with UKA, and concluded that HTO was associated with more intraoperative and postoperative complications.…”
Section: Discussionmentioning
confidence: 97%
“…13,42 In a study of 70,464 patients aged between 50 and 70 years from the Korean National Health Insurance claims database, HTO showed a higher risk of reoperation than UKA at 10-year follow-up, while postoperative DVT and SSI were significantly higher in UKA than in HTO. 19 A retrospective comparative study including patients from the Military Health System also demonstrated that HTO was associated with a higher reoperation rate when compared with UKA. 27 Stukenborg-Colsman et al 36 conducted one of the few relevant randomized controlled trials that can be identified in the literature, comparing 32 patients treated with HTO and 28 patients treated with UKA, and concluded that HTO was associated with more intraoperative and postoperative complications.…”
Section: Discussionmentioning
confidence: 97%
“…Also, postoperative recovery is generally quicker after UKA than HTO [ 23 ]. For postoperative complications, several reviews report lower rates after UKA [ 6 , 14 , 34 ], although a 2022 South Korean registry study including 21,194 UKAs and 49,270 HTOs found higher rates of deep venous thrombosis and surgical site infection after UKA [ 25 ]. Complications found in both groups in the present study are comparable to those reported in other studies.…”
Section: Discussionmentioning
confidence: 99%